Extreme Adjustments to Telehealth Services among Rural Public Health Nurses during the Covid-19 Pandemic in Padang Indonesia - Fitra Yeni; Windy Freska; Mahathir; Dally Rahman (PT FORMOSA CENDEKIA GLOBAL, 2023)
Objective: During the COVID-19 pandemic, rural community health nurses selected telehealth as a novel approach for providing health service. This research describes the interactions between public health nurses and the health service system concerning telehealth implementation. Method: Qualitative research was conducted on rural community nurses at Community Health Center of Padang, Indonesia. The sample was determined based on data saturation. The data was collected using in-depth interviews with open and semi-structured questions. The findings were analyzed utilizing thematic analysis as the primary focus. Result: An overview of telehealth implementation in rural communities is obtained in terms of device aspects, long-distance communication ethics, communication collaboration, and communication interactions in health services. Conclusion: The study’s finding demonstrate that telehealth assisted extend the reach of rural community health service. Adjusting communication patterns using communication technologies and designing the most influential information for symptom detection and education sessions represented a challenge for nurses